Dinitrogen fixation and activation by Ti and Zr atoms, clusters and complexes - Kuganathan, Navaratnarajah; Greene, Jennifer C.; Himmel, Hans-Jörg (New journal of chemistry, 2006)
This perspective deals with dinitrogen fixation and activation (a) by complexes of the early transition metals Ti and Zr as synthesized by solution techniques, and (b) by ligand-free Ti and Zr atoms and small clusters as generated using the matrix isolation technique. The two approaches are very different, and not many attempts have yet been made to connect the two different research areas, although a detailed understanding of dinitrogen activation and fixation can only be achieved if all efforts are combined. One of the most striking results that emerged from the research of one of us is that the ligand-free dimer Ti(2), which can be stabilized and studied in matrix isolation experiments, is able to cleave the strong NN triple bond without a significant activation barrier in just one step, leading to the cyclic bis-nitrido species Ti(mu-N)(2)Ti. In this perspective we are discussing possibilities to use this unusually high reactivity for catalytic processes.